2018
DOI: 10.1089/vio.2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Help: How Students' Sexual Assault Awareness, Responsibility, and Action Correlate with Bystander Intervention Behavior

Abstract: The transtheoretical model of change postulates that behavioral adoption is a result of individuals' readiness to change. Applied to prosocial bystander behavior, having greater sexual assault awareness, prevention responsibility, and action can explain students' readiness to intervene as bystanders. The purpose of this study was to examine the relationships between students' readiness to help (RTH) and their reported prosocial bystander behavior in five sexual assault risk situations. Data were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…While there are no previous studies available on the differences among the race of disclosure recipients, there is research indicating that women who identify as racial or ethnic minorities face additional barriers related to disclosing experiences of sexual violence more generally due to factors such as historical mistreatment, racism, and fear that they will experience discrimination when disclosing (Love et al, 2017). An exploratory study by Hoxmeier, O’Connor, and McMahon (2018) found that Black and Asian women were also less likely than White women to disclose their sexual victimization because of a hesitancy to appear as reflecting poorly on their racial/ethnic communities. There has been a call to better “center” the experiences of minority students when examining campus sexual violence (Linder & Harris, 2017), which should include a stronger understanding of their experiences of both making and receiving disclosures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are no previous studies available on the differences among the race of disclosure recipients, there is research indicating that women who identify as racial or ethnic minorities face additional barriers related to disclosing experiences of sexual violence more generally due to factors such as historical mistreatment, racism, and fear that they will experience discrimination when disclosing (Love et al, 2017). An exploratory study by Hoxmeier, O’Connor, and McMahon (2018) found that Black and Asian women were also less likely than White women to disclose their sexual victimization because of a hesitancy to appear as reflecting poorly on their racial/ethnic communities. There has been a call to better “center” the experiences of minority students when examining campus sexual violence (Linder & Harris, 2017), which should include a stronger understanding of their experiences of both making and receiving disclosures.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have identified a number of correlates to receiving disclosures, including individual-level factors such as gender, with women more likely to receive disclosures (Banyard et al, 2010; Paul et al, 2013; Paul et al, 2014). Studies on disclosures have looked at the race and ethnicity of those who disclose but not that of disclosure recipients (e.g., Ullman & Filipas, 2001) although the larger bystander literature on campus sexual violence has demonstrated that White students tend to report more opportunities to intervene (Hoxmeier, O’Connor, & McMahon, 2018) and fewer missed opportunities to intervene (Hoxmeier, Acock, & Flay, 2020), while Brown, Banyard, and Moynihan (2014) found that Black students reported more pro-social behavior and fewer missed intervention opportunities.…”
Section: Individual and Community Correlates To Receiving And Responding To Disclosurementioning
confidence: 99%
“…This study found that overall, women had higher levels of RTH than men, but these results were modified by several other factors such as race, college major, and experiencing sexual harassment. Other studies have examined how measures related to sexual assault prevention were related to RTH and demographic factors (Hoxmeier et al, 2018;Tredinnick & McMahon, 2021). Hoxmeier et al (2018) found that increased RTH was related to gender, as well as with prosocial bystander behaviors performed in the past.…”
Section: Rthmentioning
confidence: 99%
“…Other studies have examined how measures related to sexual assault prevention were related to RTH and demographic factors (Hoxmeier et al, 2018;Tredinnick & McMahon, 2021). Hoxmeier et al (2018) found that increased RTH was related to gender, as well as with prosocial bystander behaviors performed in the past. Tredinnick and McMahon (2021) examined a sample of athletes and discovered that those whose coaches discussed sexual violence with them had increased RTH on the Action subscale, indicating increased readiness to take action to address sexual violence.…”
Section: Rthmentioning
confidence: 99%
See 1 more Smart Citation